Well-Posedness for Fractional $(p, q)$-Difference Equations Initial Value Problem (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we investigate a class of the fractional $(p, q)$-differenceinitial value problem with the fractional $(p, q)$-integral boundary conditionswith the aid of the method of successive approximations(Picard method) andfractional $(p, q)$-Gronwall inequality, obtaining sufficient conditions for the existence, uniqueness and continuous dependence results of solutions.